Motivation as A Determinants of Job Performance of Library Staff in Selected Academic Libraries in Kwara State - Abddulraheem, Najeebat Opeyemi; Abdulrazaq, Mutalib Olanrenwaju; Nuhu, Silifat Ranti; Yusuf, Abdul Kadir Olalekan; Yahaya, Ibrahim Olarenwaju (Inkunabula: Journal of Library Science and Islamic Information, 2024)
The study investigated staff motivation as a determinant of job performance of library staff in selected academic libraries, Kwara state. The study adopted a descriptive survey design. The population of the study comprised of professional, para-professional and non-professional staff of the three selected academic libraries of 126. A total enumeration sampling technique was applied. A sample size of 126 respondents was used for the study. Questionnaire was used as data collection instrument. Data collected was analysed using descriptive statistics of frequency counts and percentages the response rate was 96.8%. The findings of the study revealed that a higher percentage of the respondents agreed that job security and mentoring motivate them to perform their job. Additionally, the findings of the study revealed that library staff members are best motivated when they are given the opportunity to use their ability. Also, on the level of motivation of library staff based on extrinsic motivators, job security is very high. Furthermore, the findings of the study revealed that majority of the respondents agreed that improved quality of service to the user, punctuality at work, work efficiency and commitment to job are the major factors that increase level of job among library staff in academic libraries. In, addition, the study also found out that majority of the respondents agreed that library working conditions; poor staff welfare and poor communication structure are the major impediments to the motivation of library staff, but job insecurity does not impede the motivation of library staff. The study recommended that university management should endeavor to eliminate various impediments to library staff motivation.